A review of trade dispute settlement in the Malaysian manufacturing sector - Laton, Mohd Zahid (2009)
Trade dispute is one of the activities in the industrial relation in Malaysia with regard to the employees and employers. In Malaysia, the trade disputes between employees and employer is still under control as compared to other developing countries in the world. Based on the past statistics, trade dispute settlement in Malaysia has been well-managed Although the manufacturing sector has contributed to the highest number of trade disputes in Malaysia, surprisingly, more than 90% of the overall disputes reached settlement. This paper presents a review of trade disputes in Malaysia, of which, only 5.7% cases have brought to the industrial actions.